Management skills and organizational development in the staff at UNHEVAL, Huánuco – 2019 - Tarazona-Chamorro, Alex M, (2020)
The objective was to determine the influence of managerial skills on the organizational development of UNHEVAL staff. Methodology. It was a quantitative study of applied, non-experimental, observational, analytical level, with a correlational and cross-sectional design. The population was made up of 280 administrative workers from which a sample of 60 workers were selected probabilistically by simple randomization. The survey technique was used and the instrument applied was an interview guide with general characteristics and a previously validated and reliable scale of managerial and organizational development skills. Ethical considerations for research were applied. The data were analyzed applying descriptive and inferential statistics. Results. In the analysis of the management skills of the UNHEVAL staff, it was found that 68.3% (41) reached the regular level for conceptual skills, 65.0 (39) had good technical skills and the same percentage possessed skills human resources in the process to achieve this competence. Organizational development had 98.3% (59) an optimal level for systematic orientation, 85.0% (51) acceptable for the incentive system and orientation to change was deficient in 38.0% (23). Orientation by results showed an optimal level in 50% (30) and in the same proportion at the acceptable level. Conclution. The managerial abilities are related to the organizational development in the administrative workers of the UNHEVAL; being significant, indicating that regular ability determines acceptable organizational development (X2 = 97.300, 2 gl and p = 0.000).